Need Analysis of Integrated Science Digital Teaching Materials with Blended Learning Models in the New Normal Era for PGMI Students throughout East Java - Rizki Amelia (UIN Siber Syekh Nurjati Cirebon, 2023)
AbstractThe Covid-19 pandemic has affected all sectors of life, including education. During the Covid-19 pandemic, all tertiary institutions changed learning process by using blended learning, including the Madrasah Ibtidaiyah Teacher Education (PGMI) study program throughout East Java. Blended learning can only be successful when paired with instructional resources tailored to each student's individual requirements. This research aims to identify and evaluate gaps in East Java's PGMI student population's access to digital scientific instruction resources that are compatible with blended learning pedagogies. This study employed a quantitative survey method involving PGMI students throughout East Java. Data were collected using questionnaires distributed online. Need analysis included learning characteristics, teaching materials, and learning orientation. Based on the analysis that has been done, it is concluded that students need interactive teaching materials based on problem-based learning equipped with virtual practicums or online students worksheets.Keywords: digital teaching materials, blended learning, new normal era.AbstrakPandemi Covid-19 telah mempengaruhi semua sektor kehidupan, termasuk pendidikan. Di masa pandemi Covid-19, seluruh perguruan tinggi mengubah proses pembelajaran dengan menggunakan blended learning, termasuk program studi Pendidikan Guru Madrasah Ibtidaiyah (PGMI) se-Jawa Timur. Blended learning hanya dapat berhasil apabila dipasangkan dengan sumber daya instruksional yang disesuaikan dengan kebutuhan individu masing-masing mahasiswa. Penelitian ini bertujuan untuk mengidentifikasi dan mengevaluasi kesenjangan akses populasi mahasiswa PGMI se-Jawa Timur terhadap sumber pengajaran sains digital yang kompatibel dengan pedagogi pembelajaran campuran. Penelitian ini menggunakan metode survei kuantitatif yang melibatkan mahasiswa PGMI se-Jawa Timur. Pengumpulan data dilakukan dengan menggunakan kuesioner yang disebarkan secara online. Analisis kebutuhan meliputi karakteristik pembelajaran, bahan ajar, dan orientasi pembelajaran. Berdasarkan analisis yang telah dilakukan, disimpulkan bahwa siswa membutuhkan bahan ajar interaktif berbasis pembelajaran berbasis masalah yang dilengkapi dengan praktikum virtual atau LKS online.Kata kunci: bahan ajar digital, blended learning, era new normal.